2007
DOI: 10.1177/1460408607086775
|View full text |Cite
|
Sign up to set email alerts
|

Liver trauma

Abstract: Management of blunt or penetrating injury to the liver remains a significant challenge to trauma surgeons. Liver injury remains common in both blunt and penetrating trauma of the abdomen. Unstable patients require immediate laparotomy. Selective patients can be managed without surgery and with careful monitoring. There has been a recent resurgence in the role of temporary packing in the management of liver trauma. Other commonly used techniques are resectional debribement and suture ligation of bleeding vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…There were previously two well-recognized mechanisms of blunt liver trauma: deceleration injury and crush injury (1,2,4). In the present study, acceleration injury has been identified as another mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were previously two well-recognized mechanisms of blunt liver trauma: deceleration injury and crush injury (1,2,4). In the present study, acceleration injury has been identified as another mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt liver trauma demands emergency treatment and remains a great challenge for surgeons (1,2). Normally, the rib cage and the vertebral column protect the liver from violent forces from outside the body; the ligaments and vena cava fix the liver in place to avoid violent movements (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful management of liver trauma dates back over two centuries with various case reports and case series detailing successful surgical and non-operative management [7], although the emphasis was on surgical intervention : Tilton's series from New York in 1905 reported a 62.5% mortality in those operated on after hepatic 'rupture' [8]. In 1908 Pringle suggested that "While small lacerations of the liver substance may be, and no doubt are, recovered from without operative interference: if the laceration be extensive and vessels of any magnitude are torn, haemorrhage will, owing to the structural arrangement of the liver, go on continuously" [9].…”
Section: History Of Managementmentioning
confidence: 99%
“…He also described the adjunct that bears his name of compressing the portal triad to limit hepatic inflow to aid liver haemostasis. Peri-hepatic packing became the management of choice for uncontrollable liver haemorrhage during World War I but liver injury had a 66% mortality rate [7] and a high incidence of post-operative infection [10]. Madding reported improved outcomes in the Second World War, and shortly afterwards in civilian practice, using early laparotomy and liver preservation (blunt suture and direct vessel ligation) or resection aided by improvements in aseptic care and critical care [10]; mortality fell to below 30%.…”
Section: History Of Managementmentioning
confidence: 99%